Publiczne wsparcie rolnictwa ze środków unijnych i krajowych w pierwszych latach członkostwa Polski w Unii Europejskiej - Więznowska, Katarzyna (Public Support of Agriculture from the European Union and Domestic Sources in the Initial Years of the Membership of Poland in the European Union, 2006)
The accession to the EU caused a substantial increase in the financial support for Polish agriculture. Financial instruments of CAP (already implemented or due to be implemented) presented in the article will improve the situation of Polish agriculture. Therefore, the probability of good usage of EU support for farmers is high. Because of the success of SAP ARD and the high interest of post-accession programs among farmers it can be stated that the level of absorption of funds will be high and all the EU funds for agriculture will be fully used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 24-32